Acceptance of dance training system based on augmented reality and technology acceptance model (TAM) - Iqbal J.; Sidhu M.S. (Springer Science and Business Media Deutschland GmbH, 2023)
Computer aided instruction; Efficiency; Engineering education; Learning systems; Object recognition; Technology transfer; Augmented reality technology; Dance learning; Dance training systems; Influential factors; Interactive system; Kinect v2; Learning efficiency; Learning Theory; Technology acceptance model; Users' acceptance; Augmented reality